(untitled) (Bangladesh Journal of Medical Science, 2017)
Aggressive angiomyxoma (AA) is a rare slow growing vulvovaginal mesenchymal neoplasm with a marked tendency for local recurrence. We here present a twenty five year old thirty two weeks primigravida patient with a large pedunculated AA arising from left side of the vulval area. We delivered the baby by caesarean section and later completely excised the tumour successfully without any signs of recurrence even after two and half years follow up. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.146-149